Kontrol Tegangan pada Sistem Hybrid Panel Surya-Turbin Angin Menggunakan Manajemen Penyimpanan Baterai - Soedibyo Soedibyo; Rezi Delfianti; Feby Agung Pamuji; Mochamad Ashari (Jurnal Rekayasa Elektrika, 2020)
The purpose of this paper is to determine the control strategy of the renewable energy systems of hybrid solar panel power and wind turbines in maximizing voltage balance. The voltage control strategy needs to be designed, mainly when different load changes occur. If it is not done, it will affect the balance of power supplied to the load and usually damage the equipment used. Solar and wind energy sources significantly influence the stability of the applied voltage’s quality due to the fluctuating nature of renewable energy. This paper proposes control strategies for the use of PIs and the signal conditioning devices that are modified using the battery charging and discharging modeling while taking into account battery lifetime using PSIM software so that optimal voltage results from hybrid solar panel and wind turbine systems are obtained. The battery will be used as energy storage when the hybrid output power is over, which will then be used again when the hybrid output power is less than the load requirement. The signal conditioning device in this study uses five power converters, one AC to DC converter, two DC-DC boost converters, one bidirectional converter, 1 DC-AC bidirectional converter. Maximum output power uses MPPT, which is applied to the boost converter, whereas to regulate the voltage through charging and discharging the battery through the bidirectional buck-boost converter. This strategy provides the appropriate voltage on the AC side.